Reforçando a segurança em ambientes VoIP que utilizam centrais telefônicas privadas - Silva, Ygor Voltolini da (2012)
This essay has the goal show how the main and most known security mechanisms act on VoIP communications. For this, the HiPath 3000 PBX line, of Siemens Enterprise, is used, to reproduce communications environments between IP subscriber lines, with ITSP authenticated using SIP protocol and, lastly, interconnected to other PBX. This study premise is instruct projectists, engineers and technicians who works in telecommunications about how to improve voice communications over internet security, avoiding password robberies, intrusion attacks and, as result, invasion on private communications.